Collaborative research to enhance a business tourism destination: a case study from Porto. Issue 2 (4th May 2021) - Marques, Jorge; Pinho, Micaela
ABSTRACT: The purpose of this study is to diagnose the business tourism segment in the city of Porto and to propose a set of strategic measures to boost its development and convert the territory into a preferred business tourism destination. The opinions of 28 local stakeholders were collected through a Delphi technique. Results show that experts consider business tourism very important for Porto, as they see it as a (i) strategic tourist product, (ii) complimentary product for leisure tourism and (iii) facilitator of entrepreneurship and business network and a booster of local and regional economy. A number of improvements were proposed to help build the brand of Porto as a business tourism destination of note: (i) more offer of large venues, (ii) collaborative cooperation between businesses to consolidate the sector, (iii) increase the supply of animation, (iv) a strong marketing strategy and building a cohesive brand and (v) increase accessibilities, connectivity and facilities. Findings have important policy implications for Porto's policymakers in understanding market dynamics and planning their business tourism strategies. Moreover, findings have a broader interest as they offer constructive insights into strategies to develop business tourism worldwide and thus provide important implications for managers, policymakers and service providers.